2017
DOI: 10.1167/17.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Early dynamics of stereoscopic surface slant perception

Abstract: Surface orientation is an important visual primitive that can be estimated from monocular or binocular (stereoscopic) signals. Changes in motor planning occur within about 200 ms after either type of signal is perturbed, but the time it takes for apparent (perceived) slant to develop from stereoscopic cues is not known. Apparent slant sometimes develops very slowly (Gillam, Chambers, & Russo, 1988; van Ee & Erkelens, 1996). However, these long durations could reflect the time it takes for the visual system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Alternatively, infragranular blob neurons may code non-disparity depth perception. 3-D depth perception does not only depend on binocular disparity, but also monocular cues, for example, the sense of perspective from blurriness of color, degree of defocus, speed of movement and overlap of objects (Caziot et al, 2017 ; McCann et al, 2018 ). Apparently, there are still many unknown circuits related to binocularity and depth perception, and blob-related functional architecture within the primate V1, but it is especially difficult to study these circuits in infragranular layers because optical imaging or multi-photon calcium imaging cannot access these layers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, infragranular blob neurons may code non-disparity depth perception. 3-D depth perception does not only depend on binocular disparity, but also monocular cues, for example, the sense of perspective from blurriness of color, degree of defocus, speed of movement and overlap of objects (Caziot et al, 2017 ; McCann et al, 2018 ). Apparently, there are still many unknown circuits related to binocularity and depth perception, and blob-related functional architecture within the primate V1, but it is especially difficult to study these circuits in infragranular layers because optical imaging or multi-photon calcium imaging cannot access these layers.…”
Section: Discussionmentioning
confidence: 99%
“…Luminance defined stimuli have a highly similar response latency of 203 msecs, indicating that both cues become available to motor systems at approximately the same time. Further, Caziot et al (2017) found that disparity cues inform judgements of surface slant more rapidly than texture gradient cues.…”
Section: Binocular Disparitymentioning
confidence: 99%
“…Although, prima facie, slant and depth describe different visual properties, they are intrinsically related: surface slant gives the variation in depth orthogonal to the axis of rotation, and, pooled estimates of local depth (e.g., from disparity) gives surface slant (see Gibson, 1950). Caziot et al (2017) found that the minimum response time required for above-chance judgements of surface slant is slower using texture gradient cues (~250 msecs), than using binocular disparity (210 msecs).…”
Section: Texture Gradientmentioning
confidence: 99%
“…Yet we found that in this area a majority of neurons are tuned to both disparity and vergence. Binocular disparities can be discriminated just as quickly as luminance 75,76 and are sufficient to sustain the orienting of attention in depth 77 . Furthermore at least in some circumstances, crossed (near) disparities more potently orient attention 78,79 .…”
Section: What Is Area Vip For?mentioning
confidence: 99%